The Brachyura (Crustacea: Decapoda) of the Deutschen Tiefsee-Expedition auf dem Dampfer ‘Valdivia’ 1898–1899: dates of publications and authorship - Low, Martyn E. Y.; Lee, Bee Yan; Ng, Peter K. L. (Zootaxa, 2017)
The consequences for the nomenclature of the Brachyura as a result of the inadvertent publication of new names in the two editions of the narrative of the Deutschen Tiefsee-Expedition auf dem Dampfer ‘Valdivia’ 1898–1899 that were published before their formal descriptions by Doflein in the scientific reports to the expedition are discussed. Both editions of the narrative are shown to have been issued in parts (Lieferungen). Accurate dates of publication for the parts of the narrative and for Doflein’s work are presented. A list of new taxon names in other groups of animals that may also have been inadvertently made available in the narrative is included.